2014
DOI: 10.1364/ol.39.005212
|View full text |Cite
|
Sign up to set email alerts
|

Robust bound state in the continuum in a nonlinear microcavity embedded in a photonic crystal waveguide

Abstract: We present a two-dimensional photonic crystal design with a microcavity of four defect dielectric rods with eigenfrequencies residing in the propagating band of directional waveguide. In the linear case for tuning of material parameters of defect rods the nonrobust bound state in the continuum (BSC) might occur. The BSC is a result of full destructive interference of resonant monopole and quadrupole modes with the same parity. A robust BSC arises in a self-adaptive way without necessity to tune the parameters … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 37 publications
1
33
0
1
Order By: Relevance
“…Although the BSCs can not be probed directly by an incident wave they are seen as collapses of Fano resonance when the BSC point is approached in the parametric space. That phenomenon was observed for scattering of EM waves by arrays of rods [30,33,37,40,44,45,51,52,81]. In this subsection we report a similar Fano resonance collapse in the differential and total cross-sections vs. frequency when the wave number k z tends to zero or the radius of the spheres approaches the BSC radius.…”
Section: Symmetry Protected Bscssupporting
confidence: 76%
“…Although the BSCs can not be probed directly by an incident wave they are seen as collapses of Fano resonance when the BSC point is approached in the parametric space. That phenomenon was observed for scattering of EM waves by arrays of rods [30,33,37,40,44,45,51,52,81]. In this subsection we report a similar Fano resonance collapse in the differential and total cross-sections vs. frequency when the wave number k z tends to zero or the radius of the spheres approaches the BSC radius.…”
Section: Symmetry Protected Bscssupporting
confidence: 76%
“…Over the last decade, it was shown that optical bound states with suppressed radiation loss may exist within the radiation continuum in open resonators [12][13][14][15][16][17][18][19][20][21][22]. These excitations are known as "embedded eigenstates", in analogy with the spatially localized electron states with "positive energy" in quantum systems [23][24][25].…”
Section: Main Textmentioning
confidence: 99%
“…The reciprocity constraint can be circumvented with a nonlinear material response [29]. Specifically, with a nonlinearity the embedded eigenstates can be pumped from the outside, ensuring that the energy stored in the resonator is precisely quantized [29] (see also [18][19][20][21]). Figure 5 local materials, next we analyze the structure of the fields in the shell [26,37].…”
Section: Main Textmentioning
confidence: 99%
“…Due to high Q-factor, optical BICs are very promising for many applications ranging from on-chip photonics and optical communications to biological sensing and photovoltaics. It has been already shown [10] that, in nonlinear materials due to the Kerr effect, a robust BIC arises in a self-adaptive way without necessity to tune the material parameters. In theory, BICs have infinite high quality factor, however, for real systems it is limited because of material absorption, technological imperfections, roughness, finite lateral size of samples and leakage into the substrate.…”
Section: Introductionmentioning
confidence: 99%